2024
DOI: 10.1001/jamaneurol.2023.4398
|View full text |Cite
|
Sign up to set email alerts
|

Neuronally Derived Extracellular Vesicle α-Synuclein as a Serum Biomarker for Individuals at Risk of Developing Parkinson Disease

Shijun Yan,
Cheng Jiang,
Annette Janzen
et al.

Abstract: IMPORTANCENonmotor symptoms of Parkinson disease (PD) often predate the movement disorder by decades. Currently, there is no blood biomarker to define this prodromal phase.OBJECTIVETo investigate whether α-synuclein in neuronally derived serum-extracellular vesicles identifies individuals at risk of developing PD and related dementia.DESIGN, SETTING, and PARTICIPANTSThis retrospective, cross-sectional multicenter study of serum samples included the Oxford Discovery, Marburg, Cologne, and Parkinson’s Progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…31−33 The performance of the single-molecule immunoassay was evaluated using α-Syn, a biomarker for neurogenerative diseases. 47,60 Herein, as can be seen from Figure 4b, the limit of detection (LoD) values of 43.36 and 173.02 aM were achieved in buffer and serum, respectively. The dynamic range was determined to be ∼0.1− 1000 fM in buffer and ∼0.5−1000 fM in serum (linear correlation coefficient: > 0.99), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…31−33 The performance of the single-molecule immunoassay was evaluated using α-Syn, a biomarker for neurogenerative diseases. 47,60 Herein, as can be seen from Figure 4b, the limit of detection (LoD) values of 43.36 and 173.02 aM were achieved in buffer and serum, respectively. The dynamic range was determined to be ∼0.1− 1000 fM in buffer and ∼0.5−1000 fM in serum (linear correlation coefficient: > 0.99), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…In our experiment, the concentration of the targeting molecules (e.g., α-Syn, to be measured) was so low that the possibility of having more than one molecule in one microdroplet (∼50 μm diameter) is negligible. Therefore, our experimental analysis can be called “single-molecule protein analysis” in such a sense. The performance of the single-molecule immunoassay was evaluated using α-Syn, a biomarker for neurogenerative diseases. , Herein, as can be seen from Figure b, the limit of detection (LoD) values of 43.36 and 173.02 aM were achieved in buffer and serum, respectively. The dynamic range was determined to be ∼0.1–1000 fM in buffer and ∼0.5–1000 fM in serum (linear correlation coefficient: > 0.99), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of focusing on quantitative levels in body fluids or tissues, detection of pathological neuronal a-syn conformation was targeted in this study [ 89 ]. Recently, another research team found that AD measurements of L1EV-synuclein in combination with specific prodromal markers, such as olfactory or cognitive deficit, possible or definite rapid eye movement sleep behavior disorder (RBD), or the glucocerebrosidase (GBA1) gene status, could be used to help substratify individuals with the highest risk of developing PD and related Lewy body diseases [ 92 ]. To facilitate early diagnosis of neurodegenerative illnesses, another study developed a screening approach that can be used in combination with other recognized subjective evaluation and imaging techniques.…”
Section: Exosomes In the Diagnosis And Treatment Of Neuropsychiatric ...mentioning
confidence: 99%